Ovid, Death and Transfiguration - Farrell, Joseph; Miller, John F.; Nelis, Damien; Schiesaro, Alessandro (Brill, 2023)
Death, the ultimate change, is an unexpected Leitmotiv of Ovid's career and reception. The eighteen contributions collected in this volume explore the theme of death and transfiguration in Ovid's own career and his posthumous reception, revealing a unity in diversity that has not been appreciated in these terms before now.